Marketing management - Kotler, Philip; Keller, Kevin Lane; Chernev, Alexander (Pearson Education Limited, 2022)
The world of marketing is changing every day ― and in order for students tohave a competitive edge, they need a text that reflects the best and mostrecent marketing theory and practices. Marketing Management collectivelyuses a managerial orientation, an analytical approach, a multidisciplinaryperspective, universal applications, and balanced coverage to distinguish itfrom all other marketing management texts out there. Unsurpassed in its breadth,depth, and relevance, the 16th Edition features a streamlinedorganization of the content, updated material, and new examples that reflectthe very latest market developments. After reading this landmark text, studentswill be armed with the knowledge and tools to succeed in the new marketenvironment around them.